External morphology of larva and polytene chromosomes of Clunio marinus Haliday, 1855 (Diptera, Chironomidae, Orthocladiinae) from two localities of the Atlantic coast - Michailova, Paraskeva (Zootaxa, 2022)
The larva of Clunio marinus Haliday is described based on field and reared material, collected along the coast of Vigo (Spain) and Helgoland (Germany). C. marinus can be easily distinguished from other known European Clunio species on the basis of some species-specific features found in fourth instar larvae. Comparison with related known Clunio species from Europe with comments on their larval morphology are given. The characteristics of the polytene chromosomes of C.marinus from Vigo are presented. The comparative external morphological analysis of the larvae from the two localities shows a certain differentiation at the external morphological level. The reasons for this differentiation are discussed.